2018
DOI: 10.1177/0272431618791291
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescents’ Adjustment at School: A Fresh Look at Grade and Gender Differences

Abstract: This study examined group differences by grade (fifth graders in elementary school and sixth graders in middle school) and gender in academic (behavioral and emotional engagement, academic self-concept, and worry) and socio-emotional adjustment (self-esteem, social satisfaction, social self-concept, and worry). Self-report data were collected from 1,003 students in the fall and spring of the school year (51.2% female, 36.7% Black, 47.2% White, 7.5% Hispanic, 5.7% Asian, 3% Other). Grade differences were null o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Although some past studies have found gender differences in ToM and school success (Brass et al, 2018;Devine & Hughes, 2013), the present study's null findings regarding gender differences support other studies that show girls and boys may be more similar than different in terms of perceived school engagement (Campbell et al, 2018;Van der Aar et al, 2018). However, compared to boys, we found that girls showed positive relations between affective ToM and student engagement.…”
Section: Gender Differencessupporting
confidence: 65%
See 1 more Smart Citation
“…Although some past studies have found gender differences in ToM and school success (Brass et al, 2018;Devine & Hughes, 2013), the present study's null findings regarding gender differences support other studies that show girls and boys may be more similar than different in terms of perceived school engagement (Campbell et al, 2018;Van der Aar et al, 2018). However, compared to boys, we found that girls showed positive relations between affective ToM and student engagement.…”
Section: Gender Differencessupporting
confidence: 65%
“…Such use of inquiry and dialogue regarding emotions and epistemic cognition or the ways that they acquire, justify, and use knowledge might help them to develop a more open attitude to another's perspective and emotions in socio-cognitive conflicts (Brass et al, 2018;Greene et al, 2018). The present results may promote the development or inclusion of programs that encourage problem-solving, conflict resolution, perspective-taking reflective thinking and metacognitive abilities that may help young adolescents to solve social-cognitive conflict and promote prosocial behaviours in the classroom (Campbell et al, 2018;Yeager, 2017).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Since their biological development begins earlier than adolescent boys (Blakemore, 2018), such developments may also prevail in the social domain. Our results could be partially explained by an increase in gender-role stereotypic expectations regarding females being more socially aware of the minds and emotions of others (Bartini, 2006; Brass, McKellar, North, & Ryan, 2019; Galambos, 2004; Yarnell et al, 2015), which affects the development of gender identity and may influence social development; that is, gender-role stereotypes suggest that girls have a greater understanding of other peoples’ mental and emotional worlds than boys (Weimer et al, 2017), and are more interpersonally oriented in general (Rose & Rudolph, 2006). Moreover, girls may experience supportive, intimate friendship earlier than boys (De Goede et al, 2009), and these rich social contacts may influence their socio-cognitive abilities.…”
Section: Discussionmentioning
confidence: 82%
“…In a study carried out by Neyzi et al (1975), it was reported that the mean age of menarche among girls was found to be 12.36 (0.01) years. Hence, sudden and rapid physical changes and puberty in the 7th grade constitute an important factor increasing the social appearance anxiety of early adolescents (Brass et al, 2019).…”
Section: Discussionmentioning
confidence: 99%